Validation of Cosmed`s FitMate™ in measuring oxygen consumption and estimating resting metabolic rate - Nieman, D. C.; Austin, M. D.; Benezra, L.; Pearce, S.; McInnis, T.; Unick, J.; Gross, S. J. (Research in Sports Medicine, 2006)
The purpose of this study was to assess the validity and reliability of the FitMate™ metabolic system (Cosmed, Rome, Italy) in measuring oxygen consumption and estimating resting metabolic rate (RMR). The FitMate™ is a new, small (20 × 24 cm) metabolic analyzer designed for measurement of oxygen consumption and energy expenditure during rest and exercise. Subjects included 60 healthy adults (N = 30 males, N = 30 females) ranging in age from 19 to 65 years (mean ± SD age, 36.9 ± 13.4 years) and body mass index (BMI) from 19.2 to 44.8 kg/m2 (27.7 ± 6.2 kg/m2). Subjects were given two 10 min RMR tests in one test session during which RMR was measured simultaneously with the Douglas bag and FitMate™ systems. No significant differences were found between Douglas bag and FitMate™ systems for oxygen consumption (242 ± 49 and 240 ± 49 ml/min, respectively, P = 0.066, r = 0.97, mean ± SD absolute difference 2.83 ± 11.68 ml/min) or RMR (1,662 ± 340 and 1,668 ± 344 kcal/day, P = 0.579, r = 0.97, mean ± SD absolute difference 5.81 ± 80.70 kcal/day). These data indicate that the FitMate™ is a reliable and valid system for measuring oxygen consumption and RMR in adults.